Mechanochromic luminescent materials of bimetallic Cu(i) complexes showing thermally activated delayed fluorescence. Issue 45 (26th October 2020) - Chen, Xing-Wei; He, Li-Hua; Ju, Peng; Chen, Jing-Lin; Liu, Sui-Jun; Wen, He-Rui
Abstract : Reversible mechanochromism is related to the breaking and restoring of hydrogen-bonding and luminescence color is tunable via the substituent. Abstract : Mechanochromic luminescence has recently received increasing interest due to its promising applications. Herein we report a new series of ionic bimetallic Cu(i ) complexes exhibiting reversible mechanochromic luminescence and thermally activated delayed fluorescence. These Cu(i ) complexes possess one emissive [{Cu(N^N)}2 (μ-dppm)2 ] 2+ cation with two N–H groups in two functional 3-(2′-pyridyl)pyrazole (N^N) ligands, and each N–H proton forms a N–H⋯O hydrogen bond with one O atom of a counterion ClO4 − . It is shown that reversible mechanochromic luminescence is relevant to the breaking and restoring of the NH⋯O hydrogen bonds controlled by mechanical grinding and CH2 Cl2 vapor, which is well supported by their FT-IR analyses. Importantly, the difference of those two inter-convertible luminous colors appearing in luminescence mechanochromism can be effectively regulated by altering the electronic nature of the substituent on the pyrazole ring such as the trifluoromethyl and tert -butyl. This clearly suggests that rationally designed Cu(i ) luminescent complexes can become promising candidates for developing low-cost intelligent responsive luminescence materials.